LAGU âJAR OF THE HEARTâ OLEH CHRISTINA PERRY (SEBUAH ANALISIS WACANA) - Widyahening, Ch. Evy Tri (Widya Wacana, 2015)
Discourse Analysis is one of the subject matters in the seventh semester in EnglishDepartment, Teacher Training and Education Faculty, Slamet Riyadi University. In this research,the researchers conducted Discourse Analysis for one English song. This research is aimed topeel up the content of the songs, which was sung by Christina Perri, from the perspectives ofmeaning, purpose, and the vision of the writer. Contextual aspects and inferential meaning canbe seen from that song. Grammatical aspects and lexical meaning are used to see the cohesionand coherence of this song.This research is library research. Then, it used Miles and Hubermanâs theory ofqualitative data analysis. The location of the research was in libraries of Unisri, UNS, UGM,and Balai Bahasa Semarang. The output of this research are: (1) to publish an article inscientific journal which has ISSN (after finishing the research in one semester).; (2) to report theresearch result that can be used as a reference for students who study Discourse Analysis inEnglish Department, Teacher Training and Education Faculty, Unisri.The research result shows that there were contextual aspects and inferential meaning,grammatical aspects and lexical meaning in the songs of âJar of The Heartâ by Christina Perriwhich is obtained by conducting Discourse Analysis.Key Words: Coherent, Cohesion, Context and Inferential, Discourse Analysis, Christina Perri,and Demi Lovato.